Lived experiences of school counselors of LGBTQ students - Jamora, Sheena Rose B.
This study explored the essence of the lived experiences of school counselors of LGBTQ students. Specifically, it sought to answer the research questions, “How do school counselors experience counseling LGBTQ?” and “How do school counselors help LGBTQ?”. Giorgi’s descriptive psychological phenomenological method was used to investigate the answers to these questions. Four school counselors were selected to be co-researchers in the study. Each co-researcher was interviewed regarding their experiences regarding the phenomenon of counseling LGBTQ students. Data resulting from these interviews were analyzed using Giorgi’s method of data analysis. Seven essential themes emerged from the analysis: embracing multiple roles, the professional and the personal, the struggles of LGBTQ, building a counseling relationship; facing challenges as counselors of LGBTQ, the counselor and their school, and walking a unique journey with LGBTQ. These themes provided meaningful descriptions of the phenomenon of counseling LGBTQ students. The essence of the lived experiences of school counselors of LGBTQ students emerged as this: school counselors of LGBTQ students face their own challenges as they accompany LGBTQ students through a tumultuous journey of self-discovery. The findings of this study revealed the need for further training of counselors when it comes to LGBTQ issues, family dynamics, practicing reflexivity as professionals, and being familiar with LGBTQ-affirmative practices. Recommendations for future research include further exploration of LGBTQ counseling, particularly from the lived experiences of LGBTQ students.